Tests of a 75 K.W. General Electric Alternator. Type ATB - Lane, William C.; Wheeler, Earl (My University, 1905)
Introduction: The generator tested is in the power plant of the Manhattan Ice, Light and Power Company, Manhattan, Kansas. Its regular work is to carry the lighting load during the second half of the night. It is belt driven by a 14” x 21,” Erie City, simple, non-condensing engine of one hundred and fifty horse power capacity at ninety five pounds steam pressure. The engine’s normal speed is one hundred and seventy eight revolutions per minute. The power is transmitted by a pulley nine feet, three inches in diameter to a twenty one inch pulley on the generator shaft. The generator is manufactured by the General Electric Company, Schenectady, New York. It is the revolving field, stationary armature type and is self-excited from a direct current shunt generator carried on the same shaft. The armature windings of the alternator are of the distributed, “Barrel” type. The core is of cast steel punchings laid together with suitable ducts to insure good ventilation through all parts. The coils are from wound and are laid on the core and held in place by beach wood wedges, which are driven into slots over the coils. This allows the speedy removal of damaged coils. As the armature is stationary, the insulation can be made more secure. It these machines the armature insulation is required to withstand four or five times the normal working pressure.
Citation: Lane, William C. and Wheeler, Earl. Tests of a 75 K.W. General Electric Alternator. Type ATB. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Discription of Alternator; Theory of Compensator; Field Flux; Theses